Drug-Eluting Stents versus Bare-Metal Stents for Treatment of Bare-Metal In-Stent Restenosis - Singh, Inder M. (2010)
OBJECTIVES: We compared the long-term outcomes of drug-eluting stents (DES) versus bare-metal stents (BMS) for treatment of bare-metal in-stent restenosis (ISR). BACKGROUND: There are no randomized trials or observational studies directly comparing the safety and efficacy of DES versus BMS for treatment of bare-metal ISR. METHODS: We examined data on all patients who underwent percutaneous coronary intervention (PCI) for ISR at Cleveland Clinic between 05/1999 and 06/2007. We compared the efficacy and safety of DES to BMS for treating bare-metal ISR. The primary end point was a composite of death, myocardial infarction (MI), or target lesion revascularization (TLR). The secondary endpoints were individual components of the primary endpoint. RESULTS: Of the 931 patients identified over 8 years, 706 had bare-metal ISR and met our study criteria. Of the 706 patients with bare-metal ISR, 362 were treated with DES and 344 with BMS. There were 230 cumulative events for a median follow-up of 3.2 years. After adjusting for 27 variables, DES were associated with lower primary endpoint compared to BMS for treatment of bare-metal ISR (21% versus 45%, adjusted hazard ratio [HR] 0.63; 95% confidence interval [CI], 0.42-0.95; p = 0.03). The individual secondary endpoint of death (8% versus 24%, p = 0.005) favored DES, but MI (3% versus 8%, p = 0.31), and TLR (13% versus 20%, p = 0.23) failed to reach statistical significance. CONCLUSIONS: In our multivariate analysis of patients with bare-metal ISR, DES use was associated with significantly lower death, MI, or TLR when compared to BMS.